2020
DOI: 10.1155/2020/7163985
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Colloidal Particles in Combinatorial Thin-Film Gradients for Magnetic Resonance Imaging and Hyperthermia

Abstract: A stable oil-in-water (O/W) magnetic emulsion was prepared by the emulsification of organic ferrofluid in an aqueous media, and its theranostic applications were investigated. The synthesis and characterization of the organic ferrofluid were carried out comprising of superparamagnetic maghemite nanoparticles with oleic acid coating stabilized in octane. Both exhibit spherical morphology with a mean size of 6 nm and 200 nm, respectively, as determined by TEM. Thermogravimetric analysis was carried out to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…The shortening of T2 relaxation is caused by the functionalization of nanoparticles by aminodextran coating that lessens particle agglomeration by increasing inter-particle spacing as apparent from Figures 5 and 6. The signal intensity of T2 images decreases with an increase in the iron concentrations and these results are in agreement with previously reported literature of MRI data [32]. A higher negative contrast was generated by specimens with higher iron concentrations.…”
Section: Mri Diagnostics Via Contrast Enhancementsupporting
confidence: 92%
See 1 more Smart Citation
“…The shortening of T2 relaxation is caused by the functionalization of nanoparticles by aminodextran coating that lessens particle agglomeration by increasing inter-particle spacing as apparent from Figures 5 and 6. The signal intensity of T2 images decreases with an increase in the iron concentrations and these results are in agreement with previously reported literature of MRI data [32]. A higher negative contrast was generated by specimens with higher iron concentrations.…”
Section: Mri Diagnostics Via Contrast Enhancementsupporting
confidence: 92%
“…The images revealed that there is no effect of polymer coating on the nanoparticle crystallite size which leads to the agglomeration of the coated sample particles. The aggregation due to the magnetic and dipolar interactions between the particles which results in wide hydrodynamic size distribution ( Figure S4) and agreement with previously reported data [32]. SEM and TEM images are also consistent in terms of aggregation of the samples, independent of AMD-coating.…”
Section: Size and Surface Morphologysupporting
confidence: 91%
“…127 Heating efficiency of magnetic colloidal nanoparticles emulsified by sodium dodecyl sulphate (SDS) aqueous solution was also evaluated, showing significant potential for therapeutic applications. 128 Water-soluble magnetite Fe 3 O 4 nanoparticles coated by Eudragit E100 (amino methacrylate copolymer) encapsulating Doxorubicin drug were explored for hyperthermia. The specific absorption rate values were also calculated and estimated to be 2.41, 2.71, and 4.28 W/g at the frequency of 259, 327, and 518 kHz and magnetic field strength of 22, 17, and 23 mT, respectively.…”
Section: Theranostic Applications Of Magnetic Nanoparticlesmentioning
confidence: 99%
“…Conventional techniques for cellular imaging through MRI involve a sample preparation regimen where cell samples are mixed with different concentrations of a known contrast agent and placed inside agarose pockets before imaging. A gradient thin film capable of producing a significant contrast difference along the gradient will eliminate the need for such sample preparation steps and allow for a simple and quick surface-based imaging method (Khizar et al 2020). Thin film gradients using the layer-by-layer technique which can be a promising technique in the future for disposable lab-on-chip as a dipstick approach for ultrasensitive molecular imaging of bioanalytes.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed materials chip is composed of a gradient thin film of colloidal core-shell magnetic nanoparticles that serve as exogenous contrast agents to generate a negative contrast in aqueous environments in an MRI (Khizar et al 2020). The unique core-shell morphology of these colloids coupled with adequately tailored magnetic properties can significantly increase the signal-to-noise ratio and consequently, the sensitivity of the MR images.…”
Section: Introductionmentioning
confidence: 99%